1991
DOI: 10.1021/bi00113a014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface amino acid replacements in cytochrome c peroxidase on complex formation with cytochrome c

Abstract: Site-directed mutagenesis was employed to examine the role played by specific surface residues in the activity of cytochrome c peroxidase. The double charge, aspartic acid to lysine, point mutations were constructed at positions 37, 79, and 217 on the surface of cytochrome c peroxidase, sites purported to be within or proximal to the recognition site for cytochrome c in an electron-transfer productive complex formed by the two proteins. The resulting mutant peroxidases were examined for catalytic activity by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 48 publications
(58 reference statements)
8
65
0
Order By: Relevance
“…In the case of a direct titration experiment, this causes little problem because the corresponding equation is only quadratic [4,5], and the physically meaningful root can be easily identified. In the case of a competitive displacement experiment, however, the corresponding equation becomes cubic and thus one would be faced with the possible existence of multiple roots [8,12]. A similar problem was also encountered in the determination of a dissociation constant for the recepto~ non-radioactive ligand complex from displacement curves [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a direct titration experiment, this causes little problem because the corresponding equation is only quadratic [4,5], and the physically meaningful root can be easily identified. In the case of a competitive displacement experiment, however, the corresponding equation becomes cubic and thus one would be faced with the possible existence of multiple roots [8,12]. A similar problem was also encountered in the determination of a dissociation constant for the recepto~ non-radioactive ligand complex from displacement curves [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not easy to extend the analytical, algebraically explicit description of binding equilibria to mixtures of competing ligands. For a system consisting of a protein and two competing ligands, when the total concentrations of all the components are of the same order of magnitude, combining all partial equilibria and mass conservation, one obtains a cubic algebraic equation [7,8]. Roots of polynomials degree n > 2 are usually extracted by methods of numerical analysis …”
Section: Introductionmentioning
confidence: 99%
“…The shielding effect on residues 221 and 224 must therefore arise from multiple binding sites, or long-range conformational effects. Corin et al (1991Corin et al ( , 1993 have found that substitution of Asp-79 or Asp-217 with Lys led to only relatively subtle effects on binding, steady-state electron transfer activity, and intracomplex electron transfer, indicating that these residues are probably not directly involved in the interaction domain. However, substitution of Asp-37 with Lys reduced both the binding strength and the steadystate electron transfer activity more than 10-fold.…”
Section: Discussionmentioning
confidence: 99%
“…These results supported the general features of the Poulos-Kraut model, except that Asp-79 of CcP did not appear to be involved in complex formation (Bechtold & Bosshard, 1985). More recently, Corin et al (1991Corin et al ( ,1993 and Hake et al (1992) found that replacement of Asp-37 on CcP with a lysine residue greatly decreased both the binding affinity and the steady-state electron transfer activity, as predicted by the Poulos-Kraut model. However, replacement of Asp-79 or Asp-217 with a lysine residue had only very subtle effects on binding and electron transfer activity, suggesting that these residues arenot directly involved in the interaction.…”
mentioning
confidence: 91%
“…A number of other studies using computer modeling (15-17) and chemical modification (18) have identified additional residues on CcP that may be important in cytochrome c binding. These include Asp-33, Asp-37, Asp-79, and residues between positions 221-224 and 290-294 as potential interaction sites.Site-directed mutagenesis of CcP has been used to test some of the suggested locations for the cytochrome c binding sites (21)(22)(23)(24)(25)(26)(27). These studies consistently find that charge-neutralization or charge-reversal mutants of Asp-34, Asp-37, and Glu-290 inhibit cytochrome c binding while mutations at Glu-32, Glu-35, Asp-79, Asp-148, Asp-217, and Glu-291 have little effect on cytochrome c binding.…”
mentioning
confidence: 99%